2014
DOI: 10.1111/febs.12861
|View full text |Cite
|
Sign up to set email alerts
|

Edge strand engineering prevents native‐like aggregation in Sulfolobus solfataricus acylphosphatase

Abstract: b-proteins are constantly threatened by the risk of aggregation because b-sheets are inherently structured for edge-to-edge interactions. To avoid native-like aggregation, evolution has resulted in a set of strategies that prevent intermolecular b-interactions. Acylphosphatase from Sulfolobus solfataricus (Sso AcP) represents a suitable model for the study of such a process. Under conditions promoting aggregation, Sso AcP acquires a native-like conformational state whereby an unstructured N-terminal segment in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…All three mutations are located on the protein surface, and two of them are also naturally occurring in vertebrates other than human; hence they should cause little perturbation to the protein structure and stability. It is noteworthy that the effects of surface mutations introducing or removing surface charges, do not correlate simply with aggregation propensity: the V84D and Y86E mutations in acylphosphatase from S. solfataricus do not protect the protein from unfolding and aggregation 37 . Furthermore, a D to N systematic scanning in β 2m indicated that the removal of a negative charge triggers measurable effects in aggregation propensity only when the D to N mutation occurs at a specific site 38 .…”
Section: Resultsmentioning
confidence: 99%
“…All three mutations are located on the protein surface, and two of them are also naturally occurring in vertebrates other than human; hence they should cause little perturbation to the protein structure and stability. It is noteworthy that the effects of surface mutations introducing or removing surface charges, do not correlate simply with aggregation propensity: the V84D and Y86E mutations in acylphosphatase from S. solfataricus do not protect the protein from unfolding and aggregation 37 . Furthermore, a D to N systematic scanning in β 2m indicated that the removal of a negative charge triggers measurable effects in aggregation propensity only when the D to N mutation occurs at a specific site 38 .…”
Section: Resultsmentioning
confidence: 99%
“…The elegant crystal structure of hexameric β2m reveals many interesting intermolecular interactions, however such hexameric form does not aggregate under standard conditions [ 29 ], leaving open the question on which are the interactions that set the hexamer off-pathway. Specific mutations may structurally protect the protein from the aggregation pathway undertaken by the wt protein, but in parallel open new paths to amyloid formation, as recently exemplified by protective mutations on Acylphosphatase from Sulfolobus solfataricus [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The unfolded N-terminus and destabilization of the folded unit promote native-like aggregation in vivo A crucial role in the aggregation process of Sso AcP is played in vitro by the N-terminus and b-strand 4, as shown by the fact that the establishment of an intermolecular interaction between this segment and the edge b-strand 4 initiates the process (21,(26)(27)(28)(29)(30). A similarly important role for the N-terminal segment is also observed in vivo by the reduced rate of incorporation into IBs of the mutated variants lacking the N-terminal segments.…”
Section: Native-like Aggregation Of Sso Acp Can Occur In Vivomentioning
confidence: 99%
“…The b-strand 4 of Sso AcP appears to be protected only poorly against edge-to-edge interactions compared to other acylphosphatases (29). In fact, three single-point mutants of Sso AcP in which single-residue mutations introduce additional protection of b-strand 4 have been found to resist native-like aggregation but to induce self-assembly through a different mechanism (29,30).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation